Financial Sector Assessment : Bangladesh - World Bank (Washington, DC, 2013)
The Bangladesh financial system, particularly banking and microfinance, has grown and developed since 2003 against the backdrop of 6 percent average Gross Domestic Product (GDP) growth. Banks' total assets and private credit ratios to GDP have each increased by about one-third since the 2003 Financial Sector Assessment Program (FSAP). Bank deposits, as a percentage of GDP, are comparable to other South Asian countries. Private domestic banks now hold a majority of bank assets; the shares of state-owned commercial banks (SCBs) and specialized banks (SBs) have declined correspondingly. Bank branches, access to banking, and microfinance services have expanded substantially. Nonbanking financial institutions have also grown but remain small; banks s till account for over 90 percent of financial institutions' assets. Equity market listings and capitalization have grown substantially; market capitalization was equivalent to about 14 percent of GDP in December 2008. A government bond market is developing. Further sound financial development in the various parts of the financial sector, and increased access, will benefit from improvement in fundamentals: better credit information and improved legal and judicial enforcement of creditors' rights and collateral execution.